Laparoscopic Appendectomy Trans Umbilical in Nonperforated Appendicitis - Leily Mohajerzadeh; Alireza Mahdavi; Sepehr Mirsepasi; Javad Ghoroubi; Sayeh Hatefi; Nazanin Khalili; Mehdi Sarafi; Amir Mohammad Zakeri (Pediatric Surgery Research Center of Shahid Beheshti University of Medical Sciences, 2020)
Introduction: Laparoscopic appendectomy has recently been trended to be performed by using a less trocar technique. In children, appendectomy is performed more by open approach; so this study was designed to compare benefits of non-invasive laparoscopic appendectomy with usual open technique. Materials and Methods: After obtaining institutional review board approval, from 2015 to 2018, 73 children with acute, nonperforated appendicitis were treated by single-incision laparoscopic or open approach. The patients were randomized to two treatment groups: 36 patients underwent open operation, and 37 by laparoscopic approach via single-incision in umbilicus. 3 cases of laparoscopic approach were converted to open surgery and removed from the study. In patient selection, cases of complicated appendicitis confirmed by imaging modalities were excluded. The outcomes were investigated in both groups by length of operation, duration of hospital stay, presence of postoperative fever, wound infection, ileus after operation, and pelvic abscess after surgery.  Results: 73 appendectomies were carried out totally by single surgeon, 37 were single-incision laparoscopy and 36 underwent open procedure. Total anesthesia time and duration of operation showed significantly longer in the laparoscopic group. On the other hand, time to tolerate liquid diet was significantly shorter in the laparoscopic group. The duration of hospital stay showed similar duration in both groups. No mortality occurred in the study. Overall complications demonstrated no significant difference between two groups. Also there was no difference in infectious complications between the laparoscopic group and the open group Conclusion: Our study suggests that Assisted Transumbilical laparoscopic appendectomy is a reasonable alternative to open surgery for appendicitis in acute none ruptured condition. All analyzed complications were similar between the groups, suggesting that Assisted Transumbilical laparoscopic appendectomy is a suitable ingrained method in pediatric cases with appendicitis